Effect of solution viscosity on poly(caprolactone) and chitosan based nanofiber formation for drug delivery application - Hanie Azzira Mazle 1993- 637467; Naznin Sultana, supervisor 602863; Fakulti Biosains dan Kejuruteraan Perubatan 538915 (2015)
Project Paper (Sarjana Muda Kejuruteraan (Bio - Perubatan)) - Universiti Teknologi Malaysia, 2015